Investigation of damage behaviors of ECC-to-concrete interface and damage prediction model under salt freeze-thaw cycles. (30th November 2019) - Tian, Jun; Wu, Xiaowei; Zheng, Yu; Hu, Shaowei; Ren, Wei; Du, Yinfei; Wang, Wenwei; Sun, Can; Ma, Jie; Ye, Yuxiao
Highlights: Salt freeze-thaw cycles had significant negative influences on interface bonding behaviors. Occurrence of interface fracture and degradation of interface shear strength under salt freeze-thaw cycles could be significantly influenced by ECC strength grade and interface roughness. Abstract: This paper reveals an investigation of damage behaviors of ECC-to-concrete interface with various ECC strength grades and interface roughness of concrete substrate subjected to salt freeze-thaw cycles. The test results showed that salt freeze-thaw cycles had significant negative influences on bonding behaviors of ECC-to-concrete interface. The occurrence of interface fracture and degradation of interface shear strength under salt freeze-thaw cycles could be significantly influenced by ECC strength grade and interface roughness of substrate concrete. The lower ECC strength and the smoother interface always caused earlier occurrences of interface fracture under salt freeze-thaw cycles. Besides, the lower ECC strength and the smoother interface always caused earlier occurrences of a sharp decline of interface shear strength and more decrease of interface shear strength. The area erosion rate of interface under salt freeze-thaw cycles could be significantly influenced by interface roughness of substrate concrete, and the smoother interface always caused more area erosion rate of interface. Based on the micro-damage mechanism of ECC-to-concrete interface under salt freeze-thaw cycles, a damage prediction model of ECC-to-concrete interface was proposed in this paper. The model is expected to be used to predict the damage degree of ECC-to-concrete interface subjected to salt freeze-thaw cycles.